Penggarapan Ulang Ilustrasi Musik Film “Jendela” Karya Randi Pratama; Studi Karya Tugas Akhir Larasati Rahma Aditiara - Rosiana Dewi, Maria Octavia (Institut Seni Indonesia Yogyakarta, 2022)
This research aims to examine the basic idea of Larasati Rahma Aditiara in the re-create of the music illustration of the film